Engineering Electromagnetics - Ida, Nathan (Springer, 2015)
One of the main difficulties in teaching electromagnetic fields is the perception on the part of many students that electromagnetics is essentially a supportive topic. They are told that they need to study electromagnetics early in the curriculum because they will need it later to understand other topics in the electrical engineering curriculum, such as electric machines, microwaves, or communication. This, with the prevailing perception of the topic being difficult, esoteric, or boring, creates a heavy atmosphere around the subject. More often than not, this leads to self-fulfilling prophecies, and as a result, even those students who perform well do not get the full benefit of the experience such an exciting topic can impart. This is particularly sad, because electromagnetics motivates many students to enter electrical engineering. They are familiar with electromagnetic waves, electric motors, magnetic recording, and data storage, and have been exposed to hundreds of electromagnetic devices. Yet few make the connection between these and the electromagnetics they are taught. The answer is to study electromagnetics for what it is rather than in preparation for something that will happen in the future. The study of electromagnetic fields is not more difficult than any other topic in the electrical engineering curriculum and, in many ways, is more interesting and more applied. The number of applications is so vast that any attempt to summarize will easily fill a good-sized book. One can only guess the total share of electromagnetics to the industrial output. Huge turbo generators for generation of electricity, power transmission lines, electric motors, actuators, relays, radio, TV and microwave transmission and reception, magnetic storage, and even the mundane little magnet used to hold a paper note on the refrigerator are all electromagnetic in nature. It is indeed uncommon to find a device that works without relying on any electromagnetic principle or effect. One only has to ask oneself who is going to design these systems and what are the tools necessary to do so, and the answer to why one should study electromagnetics becomes self-evident. This text attempts to present electromagnetics as a topic in itself with specific objectives and specific applications. The fact that it is used as a prerequisite for other subjects is merely a consequence that those other topics are based on electromagnetics. A good theoretical understanding of the electromagnetic field equations is required for electromagnetic design. The text fulfills this need by a rigorous treatment of the theoretical aspects of electromagnetics. In addition, it treats a large number of electromagnetic applications that the student will find interesting and useful.